1984
DOI: 10.1021/ac00278a011
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of retention for small molecules in the polystyrene/chloroform system

Abstract: 2671The nature of the separatlon mechanlsm for small molecules on polystyrene gels may be partly elucldated through the use of van't Hoff plots. For a chloroform mobile phase, a varlety of tunctlonal groups (test solutes) show only excluslon effects, while two solutes (benzolc acld and phenol) distribute into the gel. A study of several small solutes used to measure pore volume lndlcates that the retentlon of deuterated moblle phase represents the border line between exclusion and partitioning, while most othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…However, recent work has shown that pure, entropycontrolled size exclusion occurs in far fewer cases than previously thought, especially for small molecules (26)(27)(28)(29)(30), and that a completely satisfactory elucidation of the SEC mechanism has yet to be demonstrated. So, in the light of these studies, the classical definition of size-dependent elution will have to be considered somewhat arbitrary in the absence of rigorous thermodynamic evidence.…”
Section: Resultsmentioning
confidence: 95%
“…However, recent work has shown that pure, entropycontrolled size exclusion occurs in far fewer cases than previously thought, especially for small molecules (26)(27)(28)(29)(30), and that a completely satisfactory elucidation of the SEC mechanism has yet to be demonstrated. So, in the light of these studies, the classical definition of size-dependent elution will have to be considered somewhat arbitrary in the absence of rigorous thermodynamic evidence.…”
Section: Resultsmentioning
confidence: 95%
“…Note that injection of the deuterated mobile phase results in a nonzero slope. As discussed earlier (3), this value (-380 cal/mol) represents the energy of interaction between the mobile phase and polymer. Since THF is a swelling, or "good", solvent for PS-DVB, the enthalpy is expected to be negative.…”
Section: Resultsmentioning
confidence: 95%
“…Equipment. The chromatographic system was identical to that described previously (3). The glass chromatographic column (Rainin Instruments) was 6 mm i.d., rather than the 15-mm type used previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation